Simulation of denitrification and ozone loss for the Actic winter 2002/2003 - Grooß, J.-U.; Günther, G.; Müller, R.; Konopka, Paul; Bausch, S.; Schlager, H.; Voigt, C.; Volk, C. M.; Toon, G. C. (EGU, 2005)
We present simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) for the Arctic winter 2002/2003. We integrated a Lagrangian denitrification scheme into the three-dimensional version of CLaMS that calculates the growth and sedimentation of nitric acid trihydrate (NAT) particles along individual particle trajectories. From those, we derive the HNO3 downward flux resulting from different particle nucleation assumptions. The simulation results show a clear vertical redistribution of total inorganic nitrogen (NOy), with a maximum vortex average permanent NOy removal of over 5 ppb in late December between 500 and 550 K and a corresponding increase of NOy of over 2 ppb below about 450 K. The simulated vertical redistribution of NOy is compared with balloon observations by MkIV and in-situ observations from the high altitude aircraft Geophysica. Assuming a globally uniform NAT particle nucleation rate of 7.8 x 10(-6) cm(-3) h(-1) in the model, the observed denitrification is well reproduced.In the investigated winter 2002/2003, the denitrification has only moderate impact ( <= 14%) on the simulated vortex average ozone loss of about 1.1 ppm near the 460 K level. At higher altitudes, above 600 K potential temperature, the simulations show significant ozone depletion through NOx-catalytic cycles due to the unusual early exposure of vortex air to sunlight.